High-resolution quantitative computed tomography demonstrates structural defects in cortical and trabecular bone in IBD patients. - Haschka, Judith; Hirschmann, Simon; Kleyer, Arnd; Englbrecht, Matthias; Faustini, Francesca; Simon, David; Figueiredo, Camille P; Schuster, Louis; Muschitz, Christian; Kocijan, Roland; Resch, Heinrich; Atreya, Raja; et al. (Journal of Crohns & Colitis, 2016)
Background and Aims To investigate the macro- and microstructural changes of bone in patients with inflammatory bowel disease (IBD) and to define the factors associated with bone loss in IBDMethods A total of148 subjects, 59 with Crohn's Disease (CD), 39 with Ulcerative Colitis (UC) and 50 healthy controls were assessed for the geometric, volumetric and microstructural properties of bone using high-resolution peripheral quantitative computed tomography. In addition, demographic and disease-specific characteristics of IBD patients were recorded.Results IBD patients and controls were comparable in age, sex and body mass index. Total (p=0.001), cortical (p<0.001) and trabecular volumetric BMD (p=0.03) were significantly reduced in IBD patients compared to healthy controls. Geometric and microstructure analysis revealed significantly lower cortical area (p=0.001) and cortical thickness (p<0.001) without differences in cortical porosity, pore volume or pore diameter. CD showed a more severe bone phenotype than UC: While cortical bone loss was observed in both diseases, CD additionally showed profound trabecular bone loss with reduced trabecular BMD (p=0.008), bone volume (p=0.008) and trabecular thickness (p=0.009).Multivariate regression models identified the diagnosis of CD, female sex, lower body mass index and the lack of remission as factors independently associated with bone loss in IBD.Conclusion IBD patients develop significant cortical bone loss impairing bone strength. Trabecular bone loss is limited to CD patients, which exhibits a more severe bone phenotype compared to UC patients.
EVALuna2:2046